Componente Qualidade do Cofinanciamento Federal da APS: Evolução do Indicador Cuidado na Gestação e Puerpério em 2025 - Rafaela Duailibe Soares; Wyllyane Rayana Chaves Carvalho; Marcos Ronad Mota Cavalcante; Danyelle Carneiro de Souza Cavalcante; Bruno Moreira Lima; Ellen Rose Santos Filgueiras; Cirlandio Coutinho de Lima; Mariana Sousa de Abreu Menezes; Rosana de Jesus Santos Martins Coutinho; Kelly Portela Sousa; Sâmara Letícia Silva de Lima (REMUNOM, 2026)
Objective: to analyze the evolution of the Care During Pregnancy and the Postpartum Period indicator, part of the Quality Component of federal co-financing for Primary Health Care, across the three four-month periods of 2025. Method: an ecological, descriptive, intra-annual historical series study based on public secondary data extracted from the Primary Health Care Information System. Family Health and Primary Health Care teams classified as Regular, Sufficient, Good, or Excellent were included. A synthetic score ranging from 0 to 10, weighted by the number of teams, was calculated for Brazil, its macro-regions, and federative units. Results: the national score increased from 6.80 in the first four-month period to 7.17 in the third. All regions improved, with the greatest increase observed in the Northeast, where the score rose from 7.04 to 7.54. Among the federative units, 26 showed improvement, with the largest increases in Piauí, Maranhão, Alagoas, and Amazonas. The proportion of teams classified as Regular decreased from 8% to 5%, while the Excellent category increased from 14% to 18%. The combined proportion of teams classified as Good or Excellent rose from 66% to 73%. Conclusion: the indicator showed favorable progress in 2025, although the magnitude of improvement differed across regions and federative units. The findings reinforce the need for territorial monitoring, improved data quality, and analysis of the indicator's components to support better care during pregnancy and the postpartum period.